2013
DOI: 10.1017/s1744133113000030
|View full text |Cite
|
Sign up to set email alerts
|

Decision making by NICE: examining the influences of evidence, process and context

Abstract: :The National Institute for Health and Clinical Excellence (NICE) provides guidance to the National Health Service (NHS) in England and Wales on funding and use of new technologies. This study examined the impact of evidence, process and context factors on NICE decisions in [2004][2005][2006][2007][2008][2009]. A data set of NICE decisions pertaining to pharmaceutical technologies was created, including 32 variables extracted from published information. A three-category outcome variable was used, defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
80
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 19 publications
(45 reference statements)
7
80
0
2
Order By: Relevance
“…48 Limitations: This study explored the decision-making across the three of the four committees which might be significant as it became evident that each of the committees -making heavily influenced by the chair, suggesting that there may be variations in recommendations by committee. Cerri and colleagues 13 found in their statistical analysis that a large majority of technological two s and one conditional or restricted yes, suggesting that the appraisals included in our study might not be typical. However, in the pilot and feasibility stages of this research a number of other technological appraisal meetings were observed and the process, at the least, appeared to be similar to those that were observed in the main study.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…48 Limitations: This study explored the decision-making across the three of the four committees which might be significant as it became evident that each of the committees -making heavily influenced by the chair, suggesting that there may be variations in recommendations by committee. Cerri and colleagues 13 found in their statistical analysis that a large majority of technological two s and one conditional or restricted yes, suggesting that the appraisals included in our study might not be typical. However, in the pilot and feasibility stages of this research a number of other technological appraisal meetings were observed and the process, at the least, appeared to be similar to those that were observed in the main study.…”
Section: Discussionmentioning
confidence: 63%
“…Certainly, the extent of information provided seems to create further complexities rather than resolving uncertainty and straightforwardly facilitating rational decision making. 42 There was common recognition that some forms of uncertainty were ignored and not addressed, as they could not be managed and that, in order to reach a decision, deliberations ultimately needed to focus down on a relatively small number of issues, with wider potentially problematic There was evidence of a plurality of legitimate perspectives for evaluating evidence, decisions and outcomes but calculative approaches in NICE decision making were particularly emphasised in the discussions on the strength of the evidence to support cost effectiveness 13 and thus the uncertainties related to that issue were paramount. One primary concern was whether the drug manufacturers analysis had been carried out using the most appropriate methodology and addressed the salient pre-agreed appraisal questions and whether the submission was transparent and accessible enough to be critically assessed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some cross-country variations are explained by considerations of therapeutic value [24], disease severity [25] and economic considerations [22,26,27]. Clinical considerations have been shown to be significant predictors of funding recommendations in Canada, the UK and Poland [28][29][30][31], with clinical uncertainty being significant in Belgium and Wales [32,33] and not significant in Scotland [34]. Cost effectiveness was a significant influence on funding recommendations in all countries except Wales [33].…”
Section: Introductionmentioning
confidence: 99%